A health data analytics maturity model for hospitals information systems. (June 2019) - Carvalho, João Vidal; Rocha, Álvaro; Vasconcelos, José; Abreu, António
Highlights: This paper present a proposal to measure Data Analytics Hospitals Information Systems maturity, to deal with complexity of Healthcare industry that created massive amounts of clinical and financial data. The Maturity Model was developed to address Hospital information systems (HIS) complexity and propose a useful tool for the demanding role of HIS management. This model was developed in line with the methodological procedures for creating maturity models, with a view to guaranteeing its recognition and relevance, both in the academic field and in society as a whole. Maturity Models in Health Analytics are a way of identifying strengths and weaknesses of HIS maturity. Abstract: In the last five decades, maturity models have been introduced as reference frameworks for Information System (IS) management in organizations within different industries. In the healthcare domain, maturity models have also been used to address a wide variety of challenges and the high demand for hospital IS (HIS) implementations. The increasing volume of data, is exceeded the ability of health organizations to process it for improving clinical and financial efficiencies and quality of care. It is believed that careful and attentive use of Data Analytics in healthcare can transform data into knowledge that can improve patient outcomes and operational efficiency. A maturity model in this conjuncture, is a way of identifying strengths and weaknesses of the HIS maturity and thus, find a way for improvement and evolution. This paper presents a proposal to measure Hospitals Information Systems maturity with regard to Data Analytics. The outcome of this paper is a maturity model, which includes six stages of HIS growth and maturity progression.